2018
DOI: 10.3389/fimmu.2018.02619
|View full text |Cite
|
Sign up to set email alerts
|

DAMP-Inducing Adjuvant and PAMP Adjuvants Parallelly Enhance Protective Type-2 and Type-1 Immune Responses to Influenza Split Vaccination

Abstract: Recently, it was reported that 2-hydroxypropyl-β-cyclodextrin (HP-β-CyD), a common pharmaceutical additive, can act as a vaccine adjuvant to enhance protective type-2 immunogenicity to co-administered seasonal influenza split vaccine by inducing host-derived damage-associated molecular patterns (DAMPs). However, like most other DAMP-inducing adjuvants such as aluminum hydroxide (Alum), HP-β-CyD may not be sufficient for the induction of protective type-1 (cellular) immune responses, thereby leaving room for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Consistent with previous reports (17,18), we showed that CpG ODN, as an adjuvant, has the potential to protect against heterologous virus challenge (Fig. 3c to f).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports (17,18), we showed that CpG ODN, as an adjuvant, has the potential to protect against heterologous virus challenge (Fig. 3c to f).…”
Section: Discussionsupporting
confidence: 93%
“…Since it is the oldest adjuvant in AIT, most facts, figures and toxicity studies are available for Al(OH) 3 . Mechanisms involved include both a depot effect (ie slow release of the allergen, formulation of the allergen as particles to target antigen‐presenting cells (APCs)) as well as interaction with the innate immune system: for example by stimulating the release of damage‐associated molecular patterns (DAMPs), by activating inflammatory DCs or by metabolic reprogramming DCs, while the previously reported dependence from inflammasome activation recently was disputed . More than 90% of all registered AIT products contain Al(OH) 3 in which the European Pharmacopoiea limits the aluminium content to 1.25 mg per parenteral dose .…”
Section: Aluminium Compoundsmentioning
confidence: 99%
“…However, one has to realize that-according to current knowledgecell death leads to release of large amounts of other DAMPs as well, which all mediate adjuvanticity. Thus, it is not a surprise that the ongoing development of novel vaccines intend to incorporate the combination of DAMP-inducing adjuvants and PAMP adjuvants [72].…”
Section: General Administration Of Damps In Vaccination Proceduresmentioning
confidence: 99%